Seminar Parenting Meningkatkan Kesadaran Orang Tua dalam Optimalisasi Tumbuh Kembang untuk Membangun Karakter Anak di TK Aisyiyah Giriroto, Boyolali, Jawa Tengah - Azizah, Annafi’ Nurul ‘Ilmi (Pengabdian Masyarakat Sumber Daya Unggul, 2024)
Parents find it difficult to change a long-established pattern of caring and become a daily habit. To that end, the purpose of this dedication is to raise the awareness of parents in the optimization of growth so that it will have an impact on the formation of the character of the child by providing comprehensive information about the stages of child development, the critical role of the parents in supporting such development, as well as effective strategies to support the growth and intellectual child and invite parents to create educational media that is easy to make when at home. The method of conducting parenting seminars with implementation measures in these activities is pre-activities, activities as well as monitoring and evaluation with interviews and observations. Parental seminars will be held on Saturday, July 27, 2024 at 8:00 PM to 12:00 PM at Giriroto Boyolali Kindergarten. Participants in this activity are a total of 55 guardians of students of A and B grades. It is hoped that through this seminar, parents will be more prepared and confident in fulfilling their roles, so that they can support their children to grow into individuals with character, independent, and ready to face the challenges of the future.